Typological Analysis of Metalhead Community’s Logo as Visual Communication During Covid-19 Pandemic - Sujud Puji Nur Rahmat; Shabri Bin Saad; Eli Irawati (Institut Seni Indonesia Yogyakarta, 2022)
Typology Analysis of Metalhead Community Logos as Visual Communication During the Covid-19 Pandemic. The Covid-19 pandemic brought many changes in terms of how to communicate within the community, namely Metalhead, both nationally and internationally by utilizing social media Facebook, Instagram, and so on through logos and graphic designs. The research problem is the tendency to use a logo which is the hallmark of the Metalhead group in terms of typography and function. Qualitative research methods with observational data collection, literature review, and documentation. The approach using typology studies includes typography and function. The findings from the results of the study show that the metalhead logo typology through digital posters has its own characteristics, in color selection, the dominant use of white in writing and the background tends to be dark in color, namely black, red, and other colors but not so dominating. Regarding letters, they tend to use unusual letters (design themselves) in writing band names. Event themes, schedules, venues, and sponsors tend to use fonts that are universally understood or still use conventional fonts in Microsoft Word. The function of the metalhead logo is to form a collective identity and communication among Metalheads and the wider community. Analisis Tipologi Logo Komunitas Metalhead sebagai Komunikasi Visual Selama Pandemik Covid-19. Masa pandemi Covid-19 membawa banyak perubahan dalam hal cara berkomunikasi di ranah komunitas yaitu Metalhead, baik secara nasional maupun internasional dengan memanfaatkan media sosial Facebook, Instagram, dan lain sebagainya lewat logo dan desain gambar. Permasalahan penelitian adalah kecenderungan penggunaan logo yang menjadi ciri khas kelompok Metalhead dalam ragam tipografi dan fungsi. Metode penelitian kualitatif dengan pengumpulan data secara observasi, kajian kepustakaan, dan dokumentasi. Pendekatan menggunakan studi tipologi mencakup tipografi dan fungsi. Temuan dari hasil penelitian memperlihatkan bahwa tipologi logo Metalhead lewat poster digital memiliki kekhasan tersendiri, dalam pemilihan warna, dominan menggunakan warna putih dalam tulisan dan latar belakang cenderung berwarna gelap yaitu hitam, warna merah, dan warna lainnya tetapi tidak begitu mendominasi. Terkait huruf, cenderung menggunakan huruf yang tidak lazim (mendesain sendiri) dalam menuliskan nama band. Tema acara, jadwal, tempat, dan sponsor cenderung menggunakan huruf yang dapat dimengerti secara universal atau masih menggunakan huruf-huruf konvensional dalam Microsoft Word. Fungsi logo Metalhead sebagai pembentuk identitas kolektif dan komunikasi di antara sesama Metalhead serta masyarakat luas.